Process for the preparation of semi-aromatic nylon by dispersion polymerization in a non-polar solvent
Patent Information
- Application Number
- CN202311081483.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-08-25
AI Technical Summary
[0003]半芳香尼龙较高的熔点导致了其较为困难的生产过程,熔融缩聚法出料困难,粘釜现象严重,产物颜色发黄甚至变黑,影响了产品的性能和正常使用
[0024] Compared to existing technologies, because nylon salts are completely insoluble in non-polar solvents, they are dispersed in powder form during polymerization, preventing polymer agglomeration and sticking to the reactor, and facilitating discharge. Furthermore, this process helps improve polymerization efficiency and effectiveness, and enhances the properties of semi-aromatic nylons.
Smart Images

Figure CN119505224B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing semi-aromatic nylon by non-polar solvent dispersion polymerization, belonging to the field of polymer material synthesis technology. Background Technology
[0002] The most significant characteristic of semi-aromatic nylon is its excellent heat resistance. Its glass transition temperature is generally above 100℃, and its melting point is generally above 250℃, mostly around 300℃. Major products include PA6T, PA9T, PA10T, and PA12T, making it an indispensable key material in aerospace, new energy, automotive manufacturing, and electronics industries.
[0003] The high melting point of semi-aromatic nylon leads to a difficult production process. Melt polycondensation is difficult to discharge, with severe sticking to the reactor, resulting in a yellow or even black color of the product, affecting its performance and normal use. Currently, the industrial production of semi-aromatic nylon mainly adopts a three-step process: salt formation, aqueous prepolymerization, and solid-phase polycondensation. The prepolymerization process is carried out in water. Due to the high solubility of nylon salts in water, the prepolymer sticks to the reactor severely, making discharge difficult. Furthermore, the molecular weight is low, requiring a longer solid-phase or liquid-phase polycondensation process to increase the molecular weight, resulting in higher production costs. (Liu Minying et al. 1. Liu Minying, Zhao Qingxiang, Fu Peng et al. A method for preparing semi-aromatic nylon: CN 101768266 A[P]; 2. Liu Minying, Xue Bingfeng, Fu Peng et al. A method for synthesizing copolymerized semi-aromatic nylon: CN 101768266 A[P]). 110885442A[P];3. Li Zhaopeng et al. Synthesis of Powdered Semi-Aromatic Nylon PA12T[J]. Polymer Bulletin, 2010(02):92-96;2. Li Kaifeng. Study on Synthesis Process of Semi-Aromatic Nylon PA12T[D]. Zhengzhou University, 2011) Semi-aromatic nylon was synthesized in two steps by salt formation-solventothermal polycondensation. The nylon salt had low solubility in the solvent used, and the synthesized semi-aromatic nylon was in powder form, which partially solved the problem of difficult discharge of semi-aromatic nylon. However, due to the strong polarity of the solvent used, the nylon salt still had a certain degree of solubility, and the sticking phenomenon was difficult to completely solve. At the same time, the solvent used contained active groups such as hydroxyl or carbonyl groups, which could partially participate in the polymerization reaction, making it difficult to obtain high molecular weight semi-aromatic nylon. Therefore, it is urgent to explore a more effective new method for preparing semi-aromatic nylon. Summary of the Invention
[0004] In view of the current state of technology, the purpose of this invention is to provide a method for preparing semi-aromatic nylon that is easy to discharge, has mild reaction conditions, completes the polymerization reaction in one step, has a short reaction time, produces products with high molecular weight, and is suitable for industrial production.
[0005] The second objective of this invention is to provide a semi-aromatic nylon prepared by the aforementioned method.
[0006] To achieve the objectives of this invention, this technology employs a salt-forming-nonpolar solvent dispersion polymerization process to synthesize semi-aromatic nylon, specifically as follows:
[0007] A method for preparing semi-aromatic nylon by dispersion polymerization in a non-polar solvent involves reacting an aliphatic diamine with an aromatic diacid to form a nylon salt; then, the nylon salt is polymerized in a non-polar solvent to obtain semi-aromatic nylon.
[0008] This invention innovatively polymerizes nylon salts in a non-soluble, non-polar solvent, which solves problems such as polymerization adhesion, low polymerization efficiency and effect, and can obtain semi-aromatic nylon with high degree of polymerization and excellent performance in one step.
[0009] In this invention, the aliphatic diamine can be any known diamine in the industry that can be used to prepare semi-aromatic nylon. For example, it can be a compound with two amino groups on the C3 to C20 aliphatic carbon chain, and can be one or more of butanediamine, pentamethylenediamine, hexanediamine, octyldiamine, nonanediamine, decanediamine, dodecyldiamine, and tridecyldiamine.
[0010] Similarly, the aromatic diacid described in this invention can also be any aromatic diacid known in the industry that can be used to prepare semi-aromatic nylon. For example, it can be a compound with two carboxyl groups on an aromatic ring. The aromatic ring can be a benzene ring, a five-membered aromatic heterocycle, a six-membered aromatic heterocycle, and / or a fused ring formed by the fusion of two or more of the aforementioned benzene ring, five-membered aromatic heterocycle, and six-membered aromatic heterocycle.
[0011] Further, the aromatic dicarboxylic acid is at least one of phthalic acid, biphenyl acid, dicarboxylic biphenyl sulfone, and carboxylic diphenyl ether; more preferably, it is one or more of terephthalic acid, isophthalic acid, 4,4'-biphenyl acid, 4,4'-dicarboxylic biphenyl sulfone, or 4,4-carboxylic diphenyl ether.
[0012] In this invention, the nylon salt can be prepared based on known processes and operations in the industry. For example, in this invention, the salt formation reaction process is as follows: aliphatic diamine is mixed with water evenly, heated to 50-100°C, aromatic dicarboxylic acid is added under stirring until the pH value of the solution reaches 7.0-7.5, stirring is continued for 1-2 hours, then cooled to room temperature to crystallize, filtered and dried to obtain nylon salt.
[0013] In this invention, the non-polar solvent is a solvent that does not have the ability to dissolve nylon salt. This invention innovatively allows nylon salt to undergo polymerization in the non-polar solvent, which can solve the problems of easy adhesion, unsatisfactory polymerization efficiency and effect in the polymerization process of nylon salt based on a modified solid-solid polymerization method of non-polar solvent dispersion.
[0014] In this invention, the nonpolar solvent is preferably one of alkanes, benzene solvents, or a mixture thereof;
[0015] The alkane solvent can be a solvent oil. The benzene solvent can be at least one of toluene and xylene.
[0016] The preferred non-polar solvent of this invention can further form an azeotrope with the water byproduct generated during the polymerization process, thereby timely removing the water and allowing the reaction to proceed towards the polymer, directly obtaining high molecular weight semi-aromatic nylon in one step. The reaction conditions are mild, the polymerization time is shortened, and the production cost is reduced.
[0017] In this invention, the liquid-to-solid ratio of the nonpolar solvent and the nylon salt can be adjusted according to the preparation needs and scale. Considering the cost, it is preferably 0.5 to 3.0 g / mL.
[0018] In this invention, the polymerization reaction is carried out in a protective atmosphere. The protective atmosphere is at least one of nitrogen, an inert gas, and carbon dioxide.
[0019] In this invention, the temperature of the polymerization reaction process is 200–260°C, and the pressure of the system is 1.0–5.0 MPa.
[0020] In this invention, the polymerization time under heat and pressure is 1 to 5 hours.
[0021] The present invention also provides a semi-aromatic nylon prepared by the method described above.
[0022] Based on the innovative preparation method described above, this invention provides a controllable approach that helps to obtain semi-aromatic nylons with special segment characteristics and excellent performance.
[0023] Beneficial effects:
[0024] Compared to existing technologies, because nylon salts are completely insoluble in non-polar solvents, they are dispersed in powder form during polymerization, preventing polymer agglomeration and sticking to the reactor, and facilitating discharge. Furthermore, this process helps improve polymerization efficiency and effectiveness, and enhances the properties of semi-aromatic nylons. Attached Figure Description
[0025] Figure 1 This is a sample of semi-aromatic nylon PA10T powder synthesized in Example 1.
[0026] Figure 2 This is the DSC heating and cooling curve of the semi-aromatic nylon PA10T sample synthesized in Example 1. Detailed Implementation
[0027] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0028] It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0029] The method for preparing semi-aromatic nylon by non-polar solvent dispersion polymerization according to the present invention involves reacting an aliphatic diamine and an aromatic diacid to form a salt to obtain a nylon salt; then, the nylon salt is polymerized in a non-polar solvent to obtain semi-aromatic nylon.
[0030] A typical preparation embodiment of the present invention may include the following steps:
[0031] 1) Synthesis of nylon salt: Mix an aliphatic diamine with 5 to 30 times its weight of water until homogeneous, heat to 50 to 100°C, add an aromatic dicarboxylic acid while stirring until the pH of the solution reaches 7.0 to 7.5, continue stirring for 1 to 2 hours, cool to room temperature to crystallize, filter and dry to obtain nylon salt.
[0032] (2) Preparation of semi-aromatic nylon: The obtained nylon salt and non-polar solvent are added to the polymerization reactor in a certain ratio (0.5-3.0 g / mL). After the oxygen is removed by inert gas, the temperature is slowly raised to 200-260℃, and the pressure inside the reactor is maintained at 1.0-5.0 MPa. After 1-5 hours, the gas is released, the solvent and the water generated in the reaction are recovered, and the pressure inside the reactor is reduced to normal pressure within 2-6 hours. The product is discharged and dried to obtain powdered semi-aromatic nylon product.
[0033] The aromatic dicarboxylic acid mentioned in step (1) is one or more of terephthalic acid, isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-dicarboxylic biphenyl sulfone or 4,4-carboxylic diphenyl ether.
[0034] The aliphatic diamine mentioned in step (1) is one or more of butanediamine, pentanediamine, hexanediamine, octanediamine, nonanediamine, decanediamine, dodecyldiamine, and tridecyldiamine.
[0035] The solvent mentioned in step (2) is one of alkane, benzene, or a mixture thereof. The alkane solvent is preferably a high-boiling-point solvent oil (e.g., its boiling point can be 60 to 200°C), and the benzene solvent is preferably toluene and xylene.
[0036] The nylon salt used in step (2) is a mixture of one or more nylon salts obtained in step (1).
[0037] The inert gas mentioned in step (2) is one of nitrogen, carbon dioxide, argon or helium.
[0038] The following are more specific and typical implementation cases:
[0039] Example 1
[0040] Mix decanediamine with 20 times its weight of water until homogeneous, heat to 90°C, add terephthalic acid while stirring until the pH of the solution reaches 7.2, continue stirring for 2 hours, cool to room temperature to crystallize, filter and dry to obtain PA10T salt.
[0041] The prepared PA10T salt and toluene were added to the polymerization reactor at a ratio of 1.0 g / mL. After purging oxygen with high-purity nitrogen, the temperature was slowly raised to 240℃, and the pressure inside the reactor was maintained at 3.5 MPa. After 2 hours, the gas was released, and the solvent and water generated in the reaction were recovered. The pressure inside the reactor was reduced to atmospheric pressure within 3 hours. The discharged product was uniformly dispersed in powder form. After drying, a powdered semi-aromatic nylon product with a relative viscosity of 2.18 was obtained.
[0042] Example 2
[0043] Mix decanediamine with 20 times its weight of water until homogeneous, heat to 100°C, add terephthalic acid while stirring until the pH of the solution reaches 7.5, continue stirring for 2 hours, cool to room temperature to crystallize, filter and dry to obtain PA10T salt.
[0044] The prepared PA10T salt and 200# solvent oil were added to the polymerization reactor at a ratio of 1.0 g / mL. After oxygen was removed with high-purity nitrogen, the temperature was slowly raised to 230℃, and the pressure inside the reactor was maintained at 3.0 MPa. After 3 hours, the gas was released, and the solvent and water generated in the reaction were recovered. The pressure inside the reactor was reduced to normal pressure within 5 hours. The discharged product was uniformly dispersed in powder form. After drying, a powdered semi-aromatic nylon product with a relative viscosity of 1.96 was obtained.
[0045] Example 3
[0046] Mix decanediamine with 30 times its weight of water until homogeneous, heat to 80°C, add terephthalic acid while stirring until the pH of the solution reaches 7.0, continue stirring for 1.5 hours, cool to room temperature to crystallize, filter and dry to obtain PA10T salt.
[0047] The prepared PA10T salt and xylene were added to the polymerization reactor at a ratio of 0.5 g / mL. After purging oxygen with high-purity nitrogen, the temperature was slowly raised to 260℃, and the pressure inside the reactor was maintained at 5.0 MPa. After 2 hours, the gas was released, and the solvent and water generated in the reaction were recovered. The pressure inside the reactor was reduced to atmospheric pressure within 6 hours. The discharged product was uniformly dispersed in powder form. After drying, a powdered semi-aromatic nylon product with a relative viscosity of 2.27 was obtained.
[0048] Example 4
[0049] Mix decanediamine with 5 times its weight of water until homogeneous, heat to 100°C, add terephthalic acid while stirring until the pH of the solution reaches 7.5, continue stirring for 2 hours, cool to room temperature to crystallize, filter and dry to obtain PA10T salt.
[0050] The prepared PA10T salt and xylene were added to the polymerization reactor at a ratio of 3 g / mL. After removing oxygen with high-purity nitrogen, the temperature was slowly raised to 210℃, and the pressure inside the reactor was maintained at 1.0 MPa. After 4 hours, the gas was released, and the solvent and water generated in the reaction were recovered. The pressure inside the reactor was reduced to atmospheric pressure within 4 hours. The discharged product was uniformly dispersed in powder form. After drying, a powdered semi-aromatic nylon product with a relative viscosity of 1.78 was obtained.
[0051] Example 5
[0052] Nonyldiamine was mixed with 20 times its weight of water and heated to 100°C. Terephthalic acid was added while stirring until the pH of the solution reached 7.2. After stirring for another 2 hours, the solution was cooled to room temperature to crystallize. The crystals were then filtered and dried to obtain PA9T salt.
[0053] The prepared PA9T salt and 150# solvent oil were added to the polymerization reactor at a ratio of 0.7 g / mL. After oxygen was removed with high-purity nitrogen, the temperature was slowly raised to 240℃, and the pressure inside the reactor was maintained at 4.0 MPa. After 2 hours, the gas was released, and the solvent and water generated in the reaction were recovered. The pressure inside the reactor was reduced to normal pressure within 4 hours. The discharged product was uniformly dispersed in powder form. After drying, a powdered semi-aromatic nylon product with a relative viscosity of 2.12 was obtained.
[0054] Example 6
[0055] Dodecyl diamine was mixed with 20 times its weight of water and heated to 100°C. Terephthalic acid was added while stirring until the pH of the solution reached 7.5. After stirring for another 2 hours, the solution was cooled to room temperature to crystallize. The crystals were then filtered and dried to obtain PA12T salt.
[0056] The prepared PA12T salt and 150# solvent oil were added to the polymerization reactor at a ratio of 1.0 g / mL. After oxygen was removed with high-purity nitrogen, the temperature was slowly raised to 230℃, and the pressure inside the reactor was maintained at 3.2 MPa. After 2 hours, the gas was released, and the solvent and water generated in the reaction were recovered. The pressure inside the reactor was reduced to atmospheric pressure within 4 hours. The discharged product was uniformly dispersed in powder form. After drying, a powdered semi-aromatic nylon product with a relative viscosity of 1.94 was obtained.
[0057] Comparative Example 1
[0058] Mix decanediamine with 20 times its weight of water until homogeneous, heat to 90°C, add terephthalic acid while stirring until the pH of the solution reaches 7.2, continue stirring for 2 hours, cool to room temperature to crystallize, filter and dry to obtain PA10T salt.
[0059] The prepared PA10T salt and ethanol were added to the polymerization reactor at a ratio of 1.0 g / mL. After removing oxygen with high-purity nitrogen, the temperature was slowly raised to 240℃, and the pressure inside the reactor was maintained at 4.0 MPa. After 2 hours, the gas was released, and the solvent and water generated in the reaction were recovered. The pressure inside the reactor was reduced to normal pressure within 3 hours. The product was discharged and dried to obtain a powdered semi-aromatic nylon product. Some of the product adhered to the stirring paddle, and the relative viscosity was measured to be 1.26.
[0060] Comparative Example 2
[0061] Mix decanediamine with 20 times its weight of water until homogeneous, heat to 90°C, add terephthalic acid while stirring until the pH of the solution reaches 7.2, continue stirring for 2 hours, cool to room temperature to crystallize, filter and dry to obtain PA10T salt.
[0062] The prepared PA10T salt and water were added to the polymerization reactor at a ratio of 1.0 g / mL. After removing oxygen with high-purity nitrogen, the temperature was slowly raised to 240℃, and the pressure inside the reactor was maintained at 3.5 MPa. After 2 hours, the gas was released, and the pressure inside the reactor was reduced to atmospheric pressure within 3 hours. Severe adhesion and agglomeration occurred inside the reactor, and the product adhered to the reactor wall and the stirring paddle, making it difficult to discharge. After drying, a semi-aromatic nylon product was obtained, and the relative viscosity was measured to be 1.51.
[0063] Test case
[0064] The high-temperature nylons prepared in Examples 1-6 and Comparative Examples 1-2 were subjected to performance tests. Tensile properties were measured according to ISO 527-1 / -2, flexural strength and flexural modulus were measured according to ISO 178, notched impact properties were measured according to ISO 180, and heat deflection temperature was measured according to ISO 75-1 / -2. The results are shown in Table 1.
[0065] Table 1
[0066]
[0067] As can be seen from Examples 1 to 6, the high-temperature nylon prepared by dispersion suspension solid-phase polymerization using high-boiling-point non-polar solvents is easy to discharge, does not clump, can reach a high relative viscosity in a short time, and the product has good performance.
[0068] Comparative Examples 1 and 2 show that when using polar, low-boiling-point solvents such as water or ethanol for dispersion polymerization, the product is prone to agglomeration, making discharge difficult, and the product has a relatively low viscosity and poor performance.
[0069] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing semi-aromatic nylon by non-polar solvent dispersion polymerization, characterized in that, Aliphatic diamines and aromatic diacids are reacted to form salts to obtain nylon salts; then, the nylon salts are polymerized in a nonpolar solvent to obtain semi-aromatic nylon. The aliphatic diamine is one or more of butanediamine, pentanediamine, hexanediamine, octanediamine, nonanediamine, decanediamine, dodecyldiamine, and tridecyldiamine; The aromatic dicarboxylic acid is a compound having two carboxyl groups on an aromatic ring; The aromatic dicarboxylic acid is at least one of phthalic acid, biphenyl dicarboxylic acid, dicarboxylic biphenyl sulfone, and carboxylic diphenyl ether; The nonpolar solvent is toluene or xylene; The polymerization reaction process takes place at a temperature of 200~260℃ and a system pressure of 1.0~5.0MPa. The polymerization time under heat and pressure is 1~5 hours.
2. The method for preparing semi-aromatic nylon by non-polar solvent dispersion polymerization as described in claim 1, characterized in that, The aromatic dicarboxylic acid is one or more of terephthalic acid, isophthalic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-dicarboxylic biphenyl sulfone, or 4,4-carboxylic diphenyl ether.
3. The method for preparing semi-aromatic nylon by non-polar solvent dispersion polymerization as described in claim 1, characterized in that, The nylon salt is PA10T salt, PA9T salt, or PA12T salt.
4. The method for preparing semi-aromatic nylon by non-polar solvent dispersion polymerization according to any one of claims 1 to 3, characterized in that, The salt formation process is as follows: aliphatic diamine is mixed with water and heated to 50~100℃. Aromatic dicarboxylic acid is added while stirring until the pH value of the solution reaches 7.0~7.
5. After stirring for 1~2 hours, the solution is cooled to room temperature to crystallize. The solution is then filtered and dried to obtain nylon salt.
5. The method for preparing semi-aromatic nylon by non-polar solvent dispersion polymerization as described in claim 1, characterized in that, The solid-liquid ratio of nylon salt and nonpolar solvent is 0.5~3.0 g / mL.
6. The method for preparing semi-aromatic nylon by non-polar solvent dispersion polymerization as described in claim 1, characterized in that, The polymerization reaction is carried out in a protective atmosphere.
7. The method for preparing semi-aromatic nylon by non-polar solvent dispersion polymerization as described in claim 6, characterized in that, The protective atmosphere is at least one of nitrogen, inert gas, and carbon dioxide.
8. A semi-aromatic nylon prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing semi-aromatic nylon
CN101768266A
Synthesis method of copolymerized semi-aromatic nylon
CN110885442A
manufacture of highly polymerized polyamides
FR1217062A
Preparation of nylon polymers
US2987507A